The Potential of Clerodendrum paniculatum Leaves Fraction as a 3-Chymotrypsin-Like (3CL) Protease Inhibitor of SARS-CoV-2 - Muhammad Arba; Arfan Arfan; Yamin Yamin; Muhammad Sulaiman Zubair (Universitas Gadjah Mada, 2023)
We described the biological activity of the Clerodendrum paniculatum leaf fraction against the SARS-CoV-2 3-Chymotrypsin-like 3CL protease at the molecular level. This study applied LC-MS/MS to identify bioactive compounds from fractions, computational studies, and fluorescence resonance energy transfer (FRET) assays to ascertain their inhibitory activity. LC-MS/MS analysis of the three samples revealed that sample 1 contained 18 compound peaks. In samples 2 and 3, there were 23 and 25 compounds with different molecular weights, respectively. Docking's study identified that the alkaloids (komarovicine and roemerine) have lower binding energies than other metabolites and standard compounds, with values of -33.47 and -32.63 kJ/mol, respectively. Roemerine demonstrated excellent stability based on dynamic simulation results and confirmed its affinity for 3CL protease predicted by the MM-PBSA approach of -89.44 kJ/mol. The FRET method for testing 3CL protease activity revealed that sample 2 had an enzyme inhibitory activity of 94.3%, which was close to that of GC376 (98.19%). Meanwhile, samples 1 and 3 yielded satisfactory inhibition activity by 89.64% and 85.24%, respectively. The antiviral activity of C. paniculatum leaves was discovered for the first time by inhibiting the 3CL protease SARS-CoV-2, providing an excellent opportunity for its development as an anti-SARS-CoV-2.